Capsidiol-related genes are highly expressed in response to Colletotrichum scovillei during Capsicum annuum fruit development stages - Baba, Viviane Y.; Powell, Adrian F.; Ivamoto-Suzuki, Suzana T. [UNESP]; Pereira, Luiz F. P.; Vanzela, Andre L. L.; Giacomin, Renata M.; Strickler, Susan R.; Mueller, Lukas A.; Rodrigues, Rosana; Goncalves, Leandro S. A. (Nature Publishing Group, 2020)
Capsicum annuum is one of the most important horticultural crops worldwide. Anthracnose disease (Colletotrichum spp.) is a major constraint for chili production, causing substantial losses. Capsidiol is a sesquiterpene phytoalexin present in pepper fruits that can enhance plant resistance. The genetic mechanisms involved in capisidiol biosynthesis are still poorly understood. In this study, a 3 ' RNA sequencing approach was used to develop the transcriptional profile dataset of C. annuum genes in unripe (UF) and ripe fruits (RF) in response to C. scovillei infection. Results showed 4,845 upregulated and 4,720 downregulated genes in UF, and 2,560 upregulated and 1,762 downregulated genes in RF under fungus inoculation. Four capsidiol-related genes were selected for RT-qPCR analysis, two 5-epi-aristolochene synthase (CA12g05030, CA02g09520) and two 5-epi-aristolochene-1,3-dihydroxylase genes (CA12g05070, CA01g05990). CA12g05030 and CA01g05990 genes showed an early response to fungus infection in RF (24 h post-inoculation-HPI), being 68-fold and 53-fold more expressed at 96 HPI, respectively. In UF, all genes showed a late response, especially CA12g05030, which was 700-fold more expressed at 96 HPI compared to control plants. We are proving here the first high-throughput expression dataset of pepper fruits in response to anthracnose disease in order to contribute for future pepper breeding programs.